2013
DOI: 10.1186/1742-2094-10-92
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of astroglial NF-kappaB enhances oligodendrogenesis following spinal cord injury

Abstract: BackgroundAstrocytes are taking the center stage in neurotrauma and neurological diseases as they appear to play a dominant role in the inflammatory processes associated with these conditions. Previously, we reported that inhibiting NF-κB activation in astrocytes, using a transgenic mouse model (GFAP-IκBα-dn mice), results in improved functional recovery, increased white matter preservation and axonal sparing following spinal cord injury (SCI). In the present study, we sought to determine whether this improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 62 publications
2
42
0
1
Order By: Relevance
“…Interestingly, TNF has been shown to have a role in the pathophysiology of autoimmune demyelinating diseases such as multiple sclerosis and experimental autoimmune encephalomyelitis (EAE) (Finsen et al, 2002) and the role of TNFR1-mediated TNF signaling in causing demyelination has been widely investigated by different authors (Arnett et al, 2001; Eugster et al, 1999; Probert et al, 2000). Finally, we and others have demonstrated that signaling mediated by transmembrane TNF, occurring mainly through TNFR2, has been proven to be essential for axon and myelin preservation and to promote remyelination (Bracchi-Richard et al, 2013; Brambilla et al, 2011; Taoufik et al, 2011). Based upon this evidence we sought to determine whether neuropathic pain-associated depression is related to hippocampal neuroplasticity and myelin alterations, and whether TNF signaling through TNFR1 plays a role in these events.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, TNF has been shown to have a role in the pathophysiology of autoimmune demyelinating diseases such as multiple sclerosis and experimental autoimmune encephalomyelitis (EAE) (Finsen et al, 2002) and the role of TNFR1-mediated TNF signaling in causing demyelination has been widely investigated by different authors (Arnett et al, 2001; Eugster et al, 1999; Probert et al, 2000). Finally, we and others have demonstrated that signaling mediated by transmembrane TNF, occurring mainly through TNFR2, has been proven to be essential for axon and myelin preservation and to promote remyelination (Bracchi-Richard et al, 2013; Brambilla et al, 2011; Taoufik et al, 2011). Based upon this evidence we sought to determine whether neuropathic pain-associated depression is related to hippocampal neuroplasticity and myelin alterations, and whether TNF signaling through TNFR1 plays a role in these events.…”
Section: Introductionmentioning
confidence: 84%
“…A possible mechanism underlying the increased expression of TNFR2 in TNFR1 −/− mice following injury could be represented by NF-κB activation through TNFR1. In a recent study we determined that in transgenic mice in which NF-κB activation is selectively inhibited in astrocytes, TNFR2 expression was significantly upregulated in the chronically injured spinal cords compared to the levels measured in the spinal cords of injured wild-type mice (Bracchi-Ricard et al, 2013). These data suggest that NF-κB activation acts as a negative regulator of TNFR2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the marker of A1 astrocytes, complement component 3 (C3), is upregulated in an NFκB-dependent manner [7]. Moreover, blocking NFκB activity in astrocytes promotes oligodendrogenesis and axonal sparing through alteration of the inflammatory environment following SCI [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, astrocytes appear to create a permissive environment that promotes OPC recruitment, migration and differentiation [172]. Accordingly, astrocytes promote oligodendrogenesis through the secretion of tissue inhibitor of metalloproteinase-1 [173, 174], and inhibition of astroglial NF-κB signaling enhances oligodendrogenesis following spinal cord injury [175]. Moreover, despite successful recruitment of OPC within a demyelinating injury in the adult rat spinal cord, these precursors fail to remyelinate the axons in the absence of astrocytes [176].…”
Section: Pathways Involved In Astrocyte-mediated Motor Neuron Toximentioning
confidence: 99%